THE DEVELOPMENT OF AUGMENTED REALITY-BASED POCKET BOOKS ON LEARNING STRAIGHT LINE 3D SHAPES USING THE MARKER BASED TRACKING METHOD - Hia, Yasifati; Indra, Zulfahmi; Haris, Denny; Nolly, Ryan Ananda (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Augmented Reality (AR) is a technology that combines 2 dimensions and 3 dimensions at the same time. Augmented Reality allows a 2-dimensional object to change into 3 dimensions with the help of devices such as cameras and smartphones. Augmented Reality has many applications, one of which is in the world of education. One example of the application of augmented reality that can be done is in the Straight Line 3D shapes topic. In this topic, Augmented Reality is used to display the spatial object in the book that was previously 2-dimensional into 3 dimensions. Markers are used as objects to be scanned via a smartphone camera. From the results of the experiment in determining the ideal distance between the camera and the marker, the ideal distance was found to be between 8 - 77 cm. This depends on the size of the marker to be scanned. The following Augmented Reality applications can run well in helping mathematics learning, especially in the topic of straight line 3D shapes.